"Dye in the Water": A Visual Approach to Communicating the Rip Current Hazard. (December 2014) - Brander, Robert W.; Drozdzewski, Danielle; Dominey-Howes, Dale
Many beaches are characterized by rip currents—strong, narrow flows that can quickly carry bathers offshore, often against their will. However, despite long-standing efforts at community education and awareness strategies, people continue to drown in rip currents at high rates. Here we describe a simple, but powerful visual-based risk communication approach involving imagery associated with releases of colored dye into rip currents that has been used as an outreach tool with success in Australia. This approach has the potential to transcend limitations of traditional education approaches and bring the rip current hazard to life for a largely unaware public.